Determinants of dental caries in deciduous teeth among Iranian school children: Evidence from a developing country - Bahareh Sadat Pezeshki; Awat Feizi; Bahareh Tahani (PLoS ONE, 2025)
Background Understanding the social determinants of oral health is essential for addressing oral health disparities and facilitating the implementation of effective oral health policies. Therefore, the aim of this study was to assess the primary dentition caries status among 7-year-old children and to explore individual- and family-level associated factors. Methods As part of a longitudinal study, this cross-sectional study was conducted between April 10 and May 8, 2024, in elementary schools in Isfahan, Iran. A valid and reliable self-administered questionnaire was distributed among 551 parents, including questions on demographic, socioeconomic, and psychological characteristics; oral health and dietary behaviors of their child; and some questions about the family status. Clinical examinations of the children were performed on-site at the schools. Based on the ICDAS II classification, six indices—including d₁–₂, d₃–₆, filled surfaces, missing surfaces, d₃–₆mfs, and d₁–₆mfs—were calculated. The correlation between factors was analyzed using Pearson and Spearman correlation coefficients. The multivariable associations of determinants were assessed using linear and logistic regression models (α = 0.05). Results Finally, 417 children were examined. More than 90% of the children had dental lesions. Based on the multiple linear regression analyses, the mean d₁–₆mfs score was significantly higher in boys (B = 6.9; 95% CI: 2.8–11.2, P = 0.01) and children attending public schools (B = 11.35; 95% CI: 6.3–16.4, P < 0.01), and lower in children with a housewife caregiver (B = –6.33; 95% CI: –11.7 to –0.95, P = 0.021) and those with a healthier diet (B = –0.25; 95% CI: –0.48 to –0.02, P = 0.029). The mean d₃–₆mfs score was also significantly lower in children with a healthier diet (B = –0.29; 95% CI: –0.5 to –0.08, P = 0.006). Based on logistic regression analysis, the odds of having a filled tooth were significantly greater in girls (OR = 2.33; 95% CI: 1.51–3.59, P < 0.001), children attending private schools (OR = 1.91; 95% CI: 1.17–3.11, P = 0.01), and children whose caregivers possessed a high school diploma (OR = 1.9; 95% CI: 1.07–3.5, P = 0.048) or a university degree (OR = 2.47; 95% CI: 1.28–4.74, P = 0.007). Conclusion The prevalence of tooth decay was high among children and was associated with demographic characteristics and socioeconomic status of the family, biological and behavioral traits of the child, and the knowledge and mental and emotional condition of the caregiver.